2021
DOI: 10.3390/jcm10245953
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 Has Affected Caregivers’ Burden of Patients with Dementia: An Exploratory Study Focusing on Coping Strategies and Quality of Life during the Lockdown

Abstract: COVID-19 has caused a public and international health emergency, leading to isolation and social distancing. These restrictions have had a significant impact on the caregivers of people with dementia, increasing the burden of patient management. The purpose of this study was to investigate the stress perceived by caregivers of patients with Alzheimer’s disease (AD) during the pandemic. We used a cross-sectional survey design to evaluate the caregivers’ psychological responses and coping strategies. Eighty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…The results indicated that HRQoL was lower in PwD CGs with higher levels of stress and anxiety related to COVID-19, which is consistent with the findings of previous studies. Previous studies have reported that QoL decreases as the COVID-19 pandemic is prolonged (Maggio et al, 2021;Tuijt et al, 2021). A qualitative study regarding the experiences of CGs under lockdown and social restrictions during the pandemic reported that CGs suffered negative impacts of restrictions, changes in living arrangements, increased cognitive and psychological difficulties, and lack of social engagement (Tuijt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results indicated that HRQoL was lower in PwD CGs with higher levels of stress and anxiety related to COVID-19, which is consistent with the findings of previous studies. Previous studies have reported that QoL decreases as the COVID-19 pandemic is prolonged (Maggio et al, 2021;Tuijt et al, 2021). A qualitative study regarding the experiences of CGs under lockdown and social restrictions during the pandemic reported that CGs suffered negative impacts of restrictions, changes in living arrangements, increased cognitive and psychological difficulties, and lack of social engagement (Tuijt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study involving PwD and their CGs found that PwD's physical health deterioration, along with CGs' changed lifestyle and reduction of healthcare services during the COVID-19 pandemic, was a factor for decreasing HRQoL in CGs (Maggio et al, 2021), supporting the results of a previous study indicating that more caregiving burden was associated with longer disease duration and more behavioral and psychological problems (Tan et al, 2019). Therefore, public health policy decision-makers need to ensure the continuity of delivery of public health interventions for family careers of PwD to reduce caregiving stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study has been published in our editorial that evaluates the psychological responses of caregivers of individuals with dementia during the COVID-19 pandemic lockdown; a cross-sectional survey using an anonymous online questionnaire was used [ 15 ].…”
Section: Everyday Lifementioning
confidence: 99%